Domination, Subordination, and the Role of Cultural Brokers in the Context of Dutch Colonial Power in Indonesia: The Case of Cisaga Plantation Industrial Landscape in West Java - Lia Nuralia; Singgih Tri Sulistiyono; Iim Imadudin; Hary Ganjar Budiman; Irfanuddin Wahid Marzuki (Culture & History Digital Journal)
This research aims to describe the dominance of power of the Dutch as colonizers over Indigenous Indonesians as the colonized. The domination of power is seen in the role of cultural brokers at the Cisaga Plantation in Ciamis, West Java, Indonesia, during the Dutch colonial period. Large plantations were the main arena of colonialist exploitation of natural resources and human labor. Domination is visible in the industrial landscape of the plantation through several built facilities. The research method used is an archaeological research method with an industrial archaeology framework through the application of Max Weber’s concept of domination. The results obtained show that there are differences in architecture, layout, as well as land height and distance between buildings. These physical conditions describe the domination and subordination of power based on social class, social status, occupation, and ethnicity. The colonialists were from the upper class and had high social status as officials and company owners of European race and white. The Indigenous Indonesians were lower class, low social status, manual workers, Asian race, and colored. The plantation officials adhered to the principle of indirect orders. The executor of the orders to the plantation workers was the Indigenous foreman as a cultural broker. In reality, the dominance of power was in the hands of the Indigenous Indonesians themselves.